Is the arbuscular mycorrhizal fungus Rhizophagus irregularis able to fulfil its life cycle in the presence of diesel pollution?. (November 2015) - Driai, Sihem; Verdin, Anthony; Laruelle, Frédéric; Beddiar, Arifa; Lounès-Hadj Sahraoui, Anissa
Abstract: The present work examined the impact of increasing diesel concentrations (0.05, 0.1, 0.25, 0.5 and 1%) on the development of both partners of the arbuscular mycorrhizal symbiosis: Rhizophagus irregularis and chicory roots ( Cichorium intybus L.) grown in vitro . Our findings showed that although the different diesel concentrations tested (0.05, 0.1, 0.25, 0.5%) affect negatively the main stages of R. irregularis development (germination, germinative hyphal elongation, root colonization rate, extraradical hyphae development, sporulation) and the chicory root growth, they are not completely inhibited, except at 1%. The arbuscular mycorrhizal fungus was able to fulfil its life cycle in the presence of the pollutant. No increase in malondialdehyde (MDA) production – a biomarker of lipid peroxidation – was detected in diesel-exposed mycorrhizal or non-mycorrhizal roots, suggesting that the negative effect of diesel on the chicory roots growth could not result from the alteration of membrane lipids. Moreover, our results pointed out that the diesel toxic effect on the growth of chicory roots is less noticeable when they are mycorrhized, indicating a protective effect of mycorrhization. This protection could be related to induction of antioxidant enzyme peroxidase activity, but not to superoxide dismutase activity. Taken together, our results demonstrated the toxic effect of diesel on the mycorrhizal symbiosis and suggest a probable involvement of the mycorrhizal fungus in the protection of chicory roots against oxidative stress induced by diesel. Highlights: Impact of diesel pollution on Rhizophagus irregularis and its host chicory roots was studied. The fungus was able to fulfil its life cycle in the presence of diesel and protect chicory roots against this pollutant. The protective effect would be due to the induction of peroxidase activity in the chicory roots. No lipid peroxidation was observed in the presence of diesel.